The safety and efficacy of periprocedural intravenous anticoagulants for acute ischemic stroke patients who underwent endovascular treatment: Sub-analysis of the RESCUE-Japan Registry 2 - Matsubara, Hirofumi; Enomoto, Yukiko; Egashira, Yusuke; Uchida, Kazutaka; Yamagami, Hiroshi; Sakai, Nobuyuki; Yoshimura, Shinichi (Journal of the Neurological Sciences, 2022)
The efficacy and safety of periprocedural anticoagulant therapy are still controversial. We investigated the effects of periprocedural anticoagulation on patients who underwent endovascular therapy (EVT) for acute ischemic stroke (AIS). The patients were dichotomized into two groups according to the use of intravenous anticoagulant during or within 24 h after EVT (AC or non-AC group). Primary outcome was defined as a modified Rankin Scale (mRS) score of 0–2 at 90 days. Safety outcomes were defined as any or symptomatic intracerebral hemorrhages (ICH). Among 1278 enrolled patients, 740 patients (57.9%) were in the AC group and the remaining 538 patients (42.1%) were in the non-AC group. The median dose of heparin was 5000 units intraoperatively, and 10,000 units /day postoperatively. In the AC group, hypercholesterolemia, higher pre-stroke modified Rankin Scale score, non-cardiac embolism etiology, higher rate of anticoagulant premedication, non-administration of t-PA (tissue plasminogen activator), later admission, and longer procedure time were observed. The rate of primary outcomes was not significantly different between the AC and non-AC groups (40.1% vs. 43.9%; adjusted odds ratio, 1.29; 95% CI, 0.96–1.73; p = 0.09). The incidence of any (26.2% vs. 25.7%; p = 0.80; adjusted odds ratio, 0.97; 95% CI, 0.72–1.22) and symptomatic (4.3% vs. 5.0%; p = 0.52; adjusted OR, 0.83; 95% CI, 0.46–1.51) intracranial hemorrhage within 72 h were not significantly different between the groups. Periprocedural anticoagulant therapy after acute revascularization did not relate to prognosis and intracranial hemorrhage after EVT. •Periprocedural anticoagulant therapy does not relate risk of ICH.•The rate of cerebral infarction can be reduced through anticoagulant therapy.•Further research is required to assess intraprocedural therapy for AIS patients.